1946
DOI: 10.1136/bmj.1.4451.639
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenicity of Penicillin-insensitive Infection

Abstract: PHYSIOLOGY OF VISION: RECENT ADVANCES MEDICAL URNA639properties of vision which up to now have been difficult to explain. One of these is the retinal direction effect of Stiles and Crawford. This aspect of the cluster hypothesis is to be dealt with in detail elsewhere. Using as test objects extremely small disks, it has been possible to identify the position of some of the clusters near the centre of a human fovea. This matter is also to be considered in detail elsewhere.Section V: The Antichromatic ResponsePh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1947
1947
1953
1953

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On the other hand, there is also evidence that strains of Staph. pyogenes exist which are naturally resistant to penicillin, having been isolated before the institution of penicillin treatment and in many instances having been shown to possess the power of inactivating penicillin by the production of penicillinase (Kirby, 1944;Spink et al, 1944aSpink et al, , 1944bBondi and Dietz, 1945;Gots, 1945;Gallardo, 1945;Harley et al, 1946). Further, it has been shown by Barber (1947aBarber ( , 1947b) that the incidence of infection with penicillin-resistant strains may be increasing, since in one hospital the percentage rose from 14.1 in 1946 to 38 in 1947.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is also evidence that strains of Staph. pyogenes exist which are naturally resistant to penicillin, having been isolated before the institution of penicillin treatment and in many instances having been shown to possess the power of inactivating penicillin by the production of penicillinase (Kirby, 1944;Spink et al, 1944aSpink et al, , 1944bBondi and Dietz, 1945;Gots, 1945;Gallardo, 1945;Harley et al, 1946). Further, it has been shown by Barber (1947aBarber ( , 1947b) that the incidence of infection with penicillin-resistant strains may be increasing, since in one hospital the percentage rose from 14.1 in 1946 to 38 in 1947.…”
Section: Discussionmentioning
confidence: 99%
“…pyogenes is, however, fairlX common, and, as Harley et al (1946) have shown, penicillinresistant staphylococci occur far more often in patients who have been in hospital some time than in new admissions. In any hospital using large quantities of penicillin (and what hospital is not nowadays ?)…”
Section: Source Of Penicillin-resistant Strainsmentioning
confidence: 99%
“…pyogenes, it seems likely (Barber and Rozwadowska-Dowzenko, 1948) that selection plays a large part in the increasing incidence of such strains in hospitals. The work of Harley et al (1946) and Forbes (1949) further makes it clear that the incidence of penicillin-resistant strains isolated from staphylococcal infections in hospital inpatients is much greater than that in out-patients. In the present study it will be seen that 20 of 49 in-patients yielded penicillin-resistant strains compared with 15 of 51 outpatients, and that there was a significantly higher incidence of penicillin-resiktant organisms in patients who had been under hospital treatment for more than a fortnight.…”
Section: Medical Journalmentioning
confidence: 99%
“…Many studies concerning the incidence of penicillin-resistant staphylococcal infection have been reported, and it is now generally agreed that this is increasing (Spink et al, 1944(Spink et al, , 1945Bondi and Dietz, 1945;Gallardo, 1945;Plough, 1945;Harley et al, 1946;Barber and Rozwadowska-Dowzenko, 1948). Results of investigations of a series of infections occurring in a single hospital, however, are difficult to assess, as such institutions often seem to be breeding-grounds of a particular strain of pathogenic staphylococcus.…”
mentioning
confidence: 99%